Improving Learning Outcomes of Human Circulatory System Materials with Picture and Picture - Dewi, Raitan; Hidayat, Saleh; Sumah, Astrid S. W. (Graduate Program Magister Manajemen Pendidikan, 2022)
The goal of this study was to see if there was an improvement in student learning outcomes in the areas of knowledge, attitudes, and abilities in the scientific subject matter of the Human Circulatory System using the Picture and Picture learning methodology for class VIII students at SMP Negeri 3 Teluk Gelam. CAR is a sort of study that is conducted in two cycles. Students from class VIII of SMP Negeri 3 Teluk Gelam participated in the study. Techniques for gathering data include both test and non-test methods. The findings revealed an increase in scientific learning outcomes for the human circulatory system content between cycles I and II.